Constructing an Alternative Concept of Islamic Governance: A Maq??idic Approach (KEMANUSIAAN The Asian Journal of Humanities, 2019)
The common perception of Islamic governance is a dark image of a non-democratic and autocratic system, or a dictatorship with iron claws, or the governance of the cleric elite with the infringement of people’s freedom under the banner of religion. This is mainly due to the fiqh? “legal positivistic” framework that is often used to explain issues concerning governance by mostly traditionalist and Islamicist scholars. Humanistic governance based on the preservation of the dignity of human beings, which has been the focal point in Islamic tenets, the inviolability of life, and responsible freedom should be explored and promoted as another alternative voice of the dominating conventional fiqh? legal positivistic hegemony. Thus, a new ijtih?d (reasoning) in dealing with the subject is absolutely mandatory. This paper will look into a new approach to governance from the “consequentialistic” approach inspired by the general theory of Maq??id al-Shar??ah. This research will explore some conceptual grounds for the exploration by looking into the epistemological dimension of governance from Islamic sources and principles through “inductive qualitative method” to critically analyse the texts, as part of the deconstruction of discourse.